The relationship between bitcoin, ethereum and nft market - Çakır, Ersel (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: The popularity of NFT tokens has started to spread to the masses as the NFT market has grown tremendously from the beginning of 2021. This study examines the relationship between the NFT market and Bitcoin and Ethereum through Chiliz, MANA and THETA. In the study, the relationship between the prices of Bitcoin, Ethereum prices and the prices of three different elements of the NFT market with high market capitalization is examined on the basis of interrelationships. Using daily data between January 2020 and June 2022, short-term dynamic Granger causality of Ethereum on Bitcoin, Granger causality of THETA on Ethereum and Granger causality of THETA on MANA are shown. However no effects of Bitcoin on Ethereum, MANA, Chiliz and THETA can be shown. The results suggest that THETA may have a causal effect both on Ethereum, which is the second largest actor in the cryptocurrency market, and on the MANA token, which is one of the important representatives of the NFT market. From this point of view, it can be said that THETA contains preliminary information about the NFT and cryptocurrency markets.

ÖZET: The popularity of NFT tokens has started to spread to the masses as the NFT market has grown tremendously from the beginning of 2021. This study examines the relationship between the NFT market and Bitcoin and Ethereum through Chiliz, MANA and THETA. In the study, the relationship between the prices of Bitcoin, Ethereum prices and the prices of three different elements of the NFT market with high market capitalization is examined on the basis of interrelationships. Using daily data between January 2020 and June 2022, short-term dynamic Granger causality of Ethereum on Bitcoin, Granger causality of THETA on Ethereum and Granger causality of THETA on MANA are shown. However no effects of Bitcoin on Ethereum, MANA, Chiliz and THETA can be shown. The results suggest that THETA may have a causal effect both on Ethereum, which is the second largest actor in the cryptocurrency market, and on the MANA token, which is one of the important representatives of the NFT market. From this point of view, it can be said that THETA contains preliminary information about the NFT and cryptocurrency markets.
Bitcoin, Ethereum ve NFT piyasası Arasındaki ilişki
Keywords: NFT Piyasası; Kriptopara Piyasası; Granger Nedenselliği; VECM; Blokzincir; NFT Market; Cryptoccurency Market; Granger Causality; VECM; Blockchain